2011
DOI: 10.1097/01367895-201122030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Current Status of Tobacco Dependence Education Curricula in US Physician Assistant Programs

Abstract: MSPurpose: Tobacco use continues to be the single most preventable cause of death and disease in the United States. A paradigm shift is needed in physician assistant (PA) education to address tobacco dependence as a chronic, relapsing disease requiring patient education, counseling, treatment, and follow-up. Methods: A national study was conducted to assess the existing tobacco dependence education currently offered in US PA programs. An established tobacco dependence curriculum survey was revised and mailed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…As with other studies in the dental 12 , 14 and medical fields, 23 , 24 our findings indicated the majority of Italian undergraduate dental hygiene programs commit a sizeable portion of the tobacco dependence curricular content and time to health effects and minimal time to treatment skills or prevention. Less than half of the respondents provided student training in tobacco treatment techniques, spending less than one hour on these important skills a year.…”
Section: Discussionsupporting
confidence: 88%
“…As with other studies in the dental 12 , 14 and medical fields, 23 , 24 our findings indicated the majority of Italian undergraduate dental hygiene programs commit a sizeable portion of the tobacco dependence curricular content and time to health effects and minimal time to treatment skills or prevention. Less than half of the respondents provided student training in tobacco treatment techniques, spending less than one hour on these important skills a year.…”
Section: Discussionsupporting
confidence: 88%
“…39 However, training consistent with a comprehensive, ED-specific model is needed because of concerns that existing curricula emphasize smoking-related health risks and neglect teaching effective strategies for behavior change. 39,40 This inconsistency leaves APPs at risk for developing cessation intervention approaches that could include scare tactics or other non-evidencebased strategies, although that was not reflected in our results.…”
Section: Discussionmentioning
confidence: 87%
“…3234 The present study is the first comprehensive assessment of MI education in all PAEA-affiliated PA programs. Although our findings establish a national benchmark for MI education, the study does have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Kelly et al 32 reported that 75.6% of PA programs in the United States included MI as part of their tobacco-dependence education curricula. However, only 79 out of 141 programs responded to that survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation